Systematic Review with Revman Method: Comparison of Creatinine Levels with Cystatin-C in Identifying CKD in Hypertension Patients - Siti Anisah Azzahra Rasmin; Abdul Mubdi Ardiansar Arifuddin Karim; Muhammad Rasyidi Juhamran (The International Journal of Medical Science and Health Research, 2025)
Background: Chronic kidney disease (CKD) is a serious complication frequently associated with hypertension. Early and accurate evaluation of kidney function is essential to prevent disease progression. Serum creatinine is commonly used to estimate glomerular filtration rate (eGFR), but its diagnostic accuracy is limited. Cystatin-C has emerged as a more sensitive and specific biomarker for detecting renal dysfunction, especially in high-risk populations such as hypertensive patients. Objective: To evaluate and compare the diagnostic accuracy of serum creatinine and cystatin-C in identifying CKD among hypertensive patients through a systematic review and meta-analysis. Methods: This systematic review followed the PRISMA guidelines and included studies retrieved from PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov. Quantitative data from 10 eligible studies were analyzed using Review Manager (RevMan) version 5.2. The primary outcomes included differences in eGFR values based on cystatin-C and creatinine, as well as diagnostic measures such as sensitivity, specificity, and area under the curve (AUC). Results: Analysis of 10 studies involving 8,554 hypertensive patients indicated that eGFR based on cystatin-C tends to yield lower estimates of kidney function compared to creatinine-based eGFR (Standardized Mean Difference [SMD] = –0.24; p = 0.12). This suggests a potential for earlier detection of kidney impairment, although the difference was not statistically significant. The majority of studies reported that cystatin-C had a higher area under the curve (AUC) and was more accurate in reclassifying CKD stages compared to creatinine. Conclusion: Cystatin-C offers superior diagnostic and predictive performance compared to creatinine in detecting CKD among hypertensive patients, especially in early detection and disease classification. Its selective use in high-risk populations is recommended to enhance diagnostic accuracy and improve clinical decision-making.